(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The paper examines the impact of digitalization on the labor market in the context of economic transformation. The main focus is on key technologies such as artificial intelligence, robotics, the Internet of Things and big data, which are creating new conditions for job creation, changing the requirements for workers’ skills and promoting process automation. The challenges associated with digitalization are analyzed, including the growth of unemployment among low-skilled personnel and the increase in economic inequality. The opportunities offered by digitalization are also identified: the development of remote work, increased productivity and the emergence of new forms of employment. Particular attention is paid to the role of the state and business in ensuring sustainable development of the labor market in the era of digitalization.